Injectable hydrogel system as well as preparation method and application thereof

By loading ZnFe-LDH and Na2S2O8NPs in injectable hydrogels to generate sulfate free radicals, the problem of the poor effect of existing ROS-mediated therapies in tumor treatment is solved, and efficient tumor cell killing and anti-tumor treatment is achieved Effect.

CN119235765APending Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411596720.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing ROS-mediated chemodynamic therapy is not ideal in tumor treatment, and is limited by insufficient endogenous H2O2 content, rapid clearance and strict Fenton reaction conditions, resulting in insufficient OH production, limiting its in biomedical on the application.

Method used

Using an injectable hydrogel system with silk fibroin as the main body, the layered metal double hydroxide ZnFe-LDH and sodium peroxygen monosulfate nanoparticles Na2S2O8NPs were loaded to generate sulfate radicals•SO4− through catalytic reaction to achieve high efficiency Generates ROS and produces oxidative damage to tumor cells.

Benefits of technology

The hydrogel system quickly forms gel near body temperature, can efficiently generate sulfate free radicals, significantly improves the killing ability of tumor cells, and achieves apoptosis of tumor cells without damaging normal cells, providing An efficient anti-tumor treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119235765A_ABST
    Figure CN119235765A_ABST
Patent Text Reader

Abstract

The invention provides an injectable hydrogel system as well as a preparation method and application thereof, and belongs to the technical field of biomedicine. According to the invention, silk fibroin is taken as a main body, layered metal double hydroxides (ZnFe-LDH) and sodium peroxymonosulfate nanoparticles (Na2S2O8 NPs) are loaded, and the concentration ratio of the ZnFe-LDH to the Na2S2O8 NPs is (1: 4)-(1: 8). The obtained injectable hydrogel system can realize rapid gelling under a body temperature condition, and has a wide application prospect in the fields of drug sustained release, tumor resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an injectable hydrogel system and a preparation method and application thereof, belonging to the field of biomedical technology. Background Art

[0002] Reactive oxygen species (ROS) play an important role in physiology. When the ROS level in tumor cells exceeds the threshold, it will cause oxidative damage to cell components, leading to further cell apoptosis or necrosis. Therefore, ROS-based tumor treatment strategies show great prospects in the medical field. At present, exogenous ROS are mainly generated by photodynamics, sonodynamics and chemodynamics in the slightly acidic tumor microenvironment. Among them, chemodynamic therapy (CDT) does not require external energy or oxygen, but mainly relies on the Fenton or Fenton-like reaction of transition metal ions with hydrogen peroxide to produce cytotoxic hydroxyl radicals (•OH). However, due to the insufficient endogenous H2O2 content in the tumor, the rapid clearance of the generated •OH, and the strict Fenton reaction conditions (pH 3~4), the therapeutic effect of •OH-mediated dynamic therapy is not ideal, which limits its further application in biomedicine.

[0003] As sulfate radicals (•SO 4− ) has emerged, ROS-mediated chemodynamic therapy can achieve good anti-tumor effects independent of the tumor microenvironment. •SO 4− Similar to the oxidation potential of •OH, its oxidative stress ability can cause direct oxidative damage to tumor cells and can also induce tumor cell apoptosis without damaging normal cells. 4− It has a longer half-life (30-40 µs), which is about 30 times longer than •OH (half-life less than 1 µs), increasing its diffusion distance in cells and effectively killing tumor cells. Usually in the pH range of 2-9, transition metal ions (iron, cobalt, copper), light or heat can activate peroxymonosulfate (PMS: ​​•HSO 5− ) and peroxodisulfate (PDS: S2O8 − ) produces • SO 4− By comparing the two sulfate radical sources, PMS is considered to be more easily activated than PDS due to its asymmetric structure. Therefore, sodium peroxymonosulfate nanoparticles (Na2S2O8NPs) are used as new ROS generators, which can efficiently enter tumor cells through endocytosis and then produce •S2O8 through step-by-step degradation. 2- , •S2O8 2-Transformed into CDT's toxic SO 4− and ·OH, leading to rapid cell lysis. However, the process of Na2S2O8NPs generating ROS is slow, and considering that the photothermal depth is limited at the tumor site, the use of the above ROS generators is not ideal. Summary of the invention

[0004] In view of this, the first purpose of the present application is to provide an injectable hydrogel system with high efficiency in generating sulfate free radicals, wherein the injectable hydrogel system can gel within 1 minute at near body temperature.

[0005] Specifically, the present application is implemented through the following scheme: An injectable hydrogel system, characterized in that: the injectable hydrogel system is mainly composed of silk fibroin and is loaded with layered metal double hydroxide ZnFe-LDH and sodium peroxymonosulfate nanoparticles Na2S2O8NPs, wherein the concentration ratio of ZnFe-LDH to Na2S2O8NPs is 1:4~1:8.

[0006] The injectable hydrogel system provided in the present application, the injectable silk fibroin hydrogel provides a three-dimensional network structure for loading and stabilizing the catalyst, can quickly gel at near body temperature and can load two nanomaterials in a relatively dispersed manner, and PMS generates sulfate radicals through catalytic reaction.

[0007] The second purpose of the applicant is to provide a method for preparing the above-mentioned injectable hydrogel system, dissolving an amino acid surfactant in an aqueous solution of layered metal double hydroxide ZnFe-LDH and activating it, adding injectable silk fibroin, and after the injectable silk fibroin is dissolved, adding an aqueous solution of sodium peroxymonosulfate nanoparticles Na2S2O8NPs, waiting until gelation occurs, to obtain an injectable hydrogel system, recorded as injectable hydrogel NSO / ZF@H.

[0008] Further, as a preference: The molecular weight of the injectable silk fibroin is 10-15 kDa (ie, the relative molecular weight is 10,000-15,000).

[0009] The preparation method of the injectable silk fibroin is as follows: boiling a Na2CO3 aqueous solution, adding silkworm cocoons and boiling, replacing a new Na2CO3 aqueous solution for boiling and degumming, washing with deionized water, drying, and obtaining degummed silk fibroin; adding a lithium bromide solution to dissolve the degummed silk fibroin to obtain a completely dissolved silk fibroin solution, placing it in a dialysis bag, and dialyzing it at room temperature; and finally freeze-drying to obtain injectable silk fibroin. Preferably, the dialysis time is 3 days, and the water is changed every 2 hours. Before dialysis, the dissolved silk fibroin solution is centrifuged to remove undissolved silk fibroin.

[0010] In the process of preparing injectable silk fibroin, the screening of target injectable silk fibroin can be achieved by controlling the specifications of the dialysis bag.

[0011] The activation temperature is 40-60°C, and the activation time is 4-6 min.

[0012] The amino acid surfactant is ethyl lauroyl arginine hydrochloride (LAE), sodium lauroyl glutamate (SLG), sodium dodecyl sulfate (SDS) or sodium cholate hydrate (SC).

[0013] In the above scheme, the preparation method of layered metal double hydroxide ZnFe-LDH is as follows: a mixed aqueous solution of NaOH and Na2CO3 is added dropwise to a mixed aqueous solution of Fe(NO3)3·9H2OH and Zn(NO3)2·6H2O within 2 h, the pH is controlled to be around 10, the obtained suspension is aged, centrifuged, washed, and vacuum dried to obtain ZnFe-LDH powder, In the mixed aqueous solution of Fe(NO3)3·9H2OH and Zn(NO3)2·6H2O, the molar ratio of Zn / Fe is 4:1-2:1.

[0014] In the above scheme, the preparation method of sodium peroxymonosulfate nanoparticles Na2S2O8NPs is as follows: add oleylamine and sodium oleate to a mixed solution of n-hexane and anhydrous ethanol, and after oleylamine and sodium oleate are completely dissolved, add ammonium persulfate, and after the ammonium persulfate is completely dissolved, centrifuge, wash (preferably wash with n-hexane and anhydrous ethanol and centrifuge), to obtain sodium peroxymonosulfate nanoparticles Na2S2O8NPs. The volume ratio of oleylamine, n-hexane, and anhydrous ethanol is 1:10:3; The mass ratio of sodium oleate to ammonium persulfate is 3:2~2:1.

[0015] In the above preparation process, low molecular weight silk fibroin (SF) was first extracted and layered double hydroxide and sodium persulfate nanoparticles were prepared; LAE was dissolved in ZnFe-LDH solution and activated at 40 °C for five minutes, cooled to room temperature and SF was added, and after SF was dissolved, Na2S2O8 solution was added, and the solution was placed in a 37 °C water bath until gelation occurred to obtain a hydrogel (ZF / NSO@H).

[0016] Na2S2O8NPs have poor stability in solution. In this application, ZnFe-LDH and Na2S2O8NPs are loaded into biocompatible injectable silk fibroin (SF) hydrogel, and the stability of Na2S2O8NPs in water can be well prolonged when transferred to an aqueous solution. The unique β-folded structure of silk fibroin enables it to exhibit excellent stability and plasticity when forming a hydrogel. Combined with the adjustable gelation conditions and structural characteristics, SF hydrogel can load a variety of active molecules and achieve sustained release or stimulus response through precise design. This is the reason why this application uses injectable silk fibroin as the main body, and it is also the basis for it to load two active components at the same time. In particular, low molecular weight SF hydrogel with a molecular weight of 10~15 kDa can not only avoid the leakage of nanoparticles during intratumoral injection, which is beneficial to the treatment of local tumors, but also ensure the rich accumulation of drugs in the tumor area and reduce side effects on normal tissues. The biocompatible amino acid surfactant, lauroyl arginine hydrochloride, is used to induce the ultra-fast gelation of SF. After the addition of ZnFe-LDH, not only can the gelation time be shortened and the solution-gel transition temperature be reduced, so that the hydrogel system provided in the present application can gel within 1 minute at near body temperature, but also the mechanical properties of the hydrogel can be improved, and the storage modulus and compression modulus of the hydrogel can be increased.

[0017] The above scheme uses silk fibroin as the main body, induces rapid gelation of silk fibroin through the amino acid active agent lauroyl arginine ethyl ester (LAE), and catalyzes sodium persulfate (Na2S2O8) nanoparticles to produce sulfate radicals by loading Zn-Fe layered double hydroxide (ZnFe-LDH). Therefore, the third purpose of this application is to provide the application of the above-mentioned injectable hydrogel system, which can be used for the preparation of drug sustained-release preparations, and can also be used for the preparation of anti-tumor preparations or anti-tumor materials.

[0018] Taking the application in the preparation of anti-tumor preparations / materials as an example, this application uses injectable silk fibroin hydrogel loaded with ZnFe-LDH and Na2S2O8NPs to generate ROS in a way that is independent of the tumor microenvironment, thereby mediating and stimulating tumor treatment. When the system is injected into the tumor, the hydrogel degrades and releases •S2O8 2- , •S2O8 2- Further generate •SO 4− and •OH, stimulating cell apoptosis to achieve the effect of tumor eradication in vivo and in vitro, realizing the efficient operation of the hydrogel system.

[0019] The present application uses a method of activating PMS with a catalyst to quickly generate a large amount of ROS. Layered metal double hydroxide ZnFe-LDH is a material with cationic metal as the main component, having a layered structure, and composed of several layers with positive charges and anions with balanced charges in the middle. The above special structure gives ZnFe-LDH good anion exchange performance and a high specific surface area, thereby showing excellent nanocatalytic performance. When the injectable silk protein-loaded ZnFe-LDH contacts Na2S2O8NPs, the metal ions (Fe) in the layered structure act as active sites to catalyze the activation process of Na2S2O8NPs. The metal ions can react with Na2S2O8NPs to generate transition state ions. These transition state ions have strong oxidizing ability and can promote the decomposition of Na2S2O8NPs to produce reactive oxygen free radicals (such as sulfate free radicals, hydroxyl free radicals, etc.). In addition, positively charged LDHs tend to interact with negatively charged cell membranes and can be more effectively delivered to tumor sites.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The injectable silk fibroin hydrogel system prepared by the present invention based on the generation of sulfate free radicals activated by ZnFe-LDH nanosheets has a certain chemodynamic killing effect on tumor cells and can be applied to chemodynamic treatment of tumors.

[0021] (2) The ZnFe-LDH nanosheets loaded in the injectable hydrogel system can activate the sulfate radicals of the attached sodium peroxymonosulfate nanoparticles Na2S2O8NPs. The silk fibroin hydrogel loaded with ZnFe-LDH and Na2S2O8NPs showed the ability to efficiently generate sulfate radicals in vitro.

[0022] (3) The present invention has low requirements for experimental instruments, and the preparation method is simple and easy to operate. The obtained hydrogel has excellent performance in mechanical properties, biocompatibility and anti-tumor properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 Transmission electron microscope images and particle size diagrams of the products ZnFe-LDH and Na2S2O8NPs obtained in Examples 1 and 2.

[0025] Figure 2The scanning electron microscope image and MAPPING of the product ZF / NSO@H obtained in Example 3.

[0026] Figure 3 This is the rheological properties diagram of the product ZF / NSO@H obtained in Example 3.

[0027] Figure 4 This is the swelling and degradation diagram of the product ZF / NSO@H obtained in Example 3.

[0028] Figure 5 This is a graph showing the in vitro active oxygen production capacity of the product ZF / NSO@H obtained in Example 3.

[0029] Figure 6 This is a diagram showing the killing effect of the product ZF / NSO@H obtained in Example 3 on tumor cells 4T1.

[0030] Figure 7 This is a diagram showing the biocompatibility effects of different concentrations of the product ZF / NSO@H obtained in Example 3. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0032] The following examples provide those of ordinary skill in the art with information on how to make and evaluate the present invention, which are merely exemplary of the present disclosure and are not intended to limit the scope. Although every effort has been made to ensure accuracy with respect to numerical values ​​(e.g., amounts, temperatures, etc.), some errors and deviations should be considered. Unless otherwise stated, temperatures are in ° C or at ambient temperature.

[0033] Example 1

[0034] To 50 mL of a mixed aqueous solution of Fe(NO3)3·9 H2O (1 mmol) and Zn(NO3)2·6 H2O (2 mmol) was added dropwise a mixed aqueous solution containing NaOH (0.35 mol / L) and Na2CO3 (0.15 mol / L). The addition time was controlled within 2 hours, and the pH of the mixed aqueous solution of Fe(NO3)3·9 H2O (1 mmol) and Zn(NO3)2·6 H2O (2 mmol) was strictly maintained at 10.0. The resulting suspension was then aged at 65°C for 24 hours. After cooling to room temperature, the product was collected by centrifugation, washed twice with deionized water and ethanol, and finally dried in vacuum at 30°C to obtain the product ZnFe-LDH.

[0035] Example 2

[0036] 20 mg of sodium oleate and 1 mL of oleylamine were dissolved in a mixed solution containing 10 mL of n-hexane and 3 mL of anhydrous ethanol. After ultrasonic dispersion, the mixture was stirred at room temperature for 10 min, and 10 mg of ammonium persulfate was added. The mixture was magnetically stirred at room temperature for 30 min. Finally, the mixture was centrifuged, washed three times with n-hexane and ethanol, and dried under vacuum to obtain the product Na2S2O8NPs.

[0037] The products ZnFe-LDH and Na2S2O8NPs obtained in Examples 1 and 2 were characterized. Figure 1 shown.

[0038] Figure 1 Figure a is a transmission electron microscope image of the product ZnFe-LDH, where it can be observed that the product is in irregular flakes; Figure 1 Figure c is the particle size distribution diagram of ZnFe-LDH. It can be seen that the particle size is uniform and the average particle size is between 100 and 200 nm.

[0039] Figure 1 (b) is the transmission image of the product Na2S2O8NPs, from which it can be observed that the product is spherical and has a high yield; Figure 1 Figure d is the particle size distribution diagram of Na2S2O8NPs. It can be seen that the particle size is uniform and the average particle size is about 200 nm.

[0040] Example 3

[0041] The preparation process of the injectable hydrogel system ZF / NSO@H in this embodiment is as follows: (1) Boil the Na2CO3 solution, add the cocoons and boil for 30 min, replace the Na2CO3 solution and boil for degumming 3 times, then wash with deionized water and dry in an oven to obtain degummed silk fibroin. Dissolve the silk fibroin in lithium bromide solution to obtain a completely dissolved silk fibroin solution (the undissolved silk fibroin is removed by centrifugation) and put it into a dialysis bag (MW : 3500), dialyzed at room temperature for 3 days, changing water every 2 hours, and finally freeze-dried to obtain low molecular weight silk fibroin (about 10 kDa).

[0042] (2) A mixed aqueous solution containing NaOH (0.35 mol / L) and Na2CO3 (0.15 mol / L) was added dropwise to a mixed aqueous solution of Fe(NO3)3·9 H2O (1 mmol) and Zn(NO3)2·6 H2O (2 mmol) in 50 mL of a mixed aqueous solution. The addition time was controlled within 2 hours, and the pH of the mixed aqueous solution of Fe(NO3)3·9 H2O (1 mmol) and Zn(NO3)2·6 H2O (2 mmol) was strictly maintained at 10.0. The resulting suspension was then aged at 65°C for 24 hours. After cooling to room temperature, the product was collected by centrifugation, washed twice with deionized water and ethanol, and finally dried in vacuum at 30°C to obtain the product ZnFe-LDH powder, denoted as: LDH.

[0043] (3) Dissolve 20 mg sodium oleate and 1 mL oleylamine in a mixed solution containing 10 mL n-hexane and 3 mL anhydrous ethanol. After ultrasonic dispersion, stir at room temperature for 10 min, add 10 mg ammonium persulfate, and stir magnetically at room temperature for 30 min. Finally, centrifuge, wash three times with n-hexane and ethanol, and vacuum dry to obtain white powder Na2S2O8NPs, denoted as: NSO.

[0044] (4) Dissolve LAE (0.15 g) in 1 mL of the aqueous solution of ZnFe-LDH prepared in step (2) (solution concentration: 100 μg mL -1 ), and then keep it at 40 °C for 5 min to complete activation. Add 0.2 g of low molecular weight SF obtained in step (1), and after SF is dissolved, add 1 mL of the aqueous solution prepared with Na2S2O8 obtained in step (3) (solution concentration: 800 μg mL -1 ), mixed evenly, and placed in a 37 ℃ water bath until gelation was achieved to obtain an injectable hydrogel system Na2S2O8NPs / ZnFe-LDH, denoted as ZF / NSO@H or NSO / LDH@H.

[0045] The performance of the injectable hydrogel system ZF / NSO@H obtained in Example 3 was tested. The results are as follows: Figures 2 to 7 shown.

[0046] Figure 2 The scanning electron microscope image and mapping image of ZF / NSO@H show that the product ZF / NSO@H has a relatively uniform pore structure and contains elements such as Zn, S, Fe, and Na, which are evenly distributed in the hydrogel.

[0047] Figure 3 Rheological properties of ZF / NSO@H Figure 3 ,Depend on Figure 3 As can be seen from a and b in the figure, the storage modulus G' of the hydrogel system ZF / NSO@H is greater than the loss modulus G'', which is consistent with the solid-like behavior of the gelation system, indicating that the three-dimensional network in the gelation system has good stability. Figure 3 It can be concluded from Figure c that the viscosity decreases with increasing shear rate, indicating that the hydrogel system has good injection performance.

[0048] Figure 4 Swelling and degradation diagram of ZF / NSOF@H. Figure 4 It can be observed in Figure a that the hydrogel system ZF / NSO@H reaches swelling equilibrium in about 30 minutes, indicating that its internal network structure can quickly adapt to the entry of water molecules, avoiding structural damage caused by long-term swelling, thereby improving the stability of the material. At the same time, the material can be released from the hydrogel more stably and controllably, avoiding the problem of too fast or too slow drug release caused by excessive swelling, which is also the basis for ZF / NSO@H in this case to be used for sustained drug release. Figure 4 As can be seen from Figure b, ZF / NSO@H is almost completely degraded in two weeks.

[0049] Figure 5 The figure shows the efficiency of ZF / NSO@H in generating sulfate radicals to degrade methylene blue (MB). It can be seen that ZF / NSO@H generates more ROS than NSO@H and has better performance in degrading MB, indicating that ZnFe-LDH can activate the ROS generated by Na2S2O8NPs more efficiently and can indeed generate sulfate radicals and hydroxyl radicals. After adding tert-butanol to capture hydroxyl radicals, the degradation rate of MB becomes lower (MB+NSO / LDH@H+TBA); after adding ethanol to capture sulfate radicals and hydroxyl radicals, the degradation rate of MB is even lower (MB+NSO / LDH@H+ EtOH), which further indicates that in the above process, ZF / NSO@H hydrogel is the source of sulfate radicals.

[0050] Figure 6 The figure shows the killing effect of ZF / NSO@H on tumor cells 4T1. The results show that different materials have different killing effects on 4T1 tumor cells. Under the catalytic action of ZnFe-LDH, ZF / NSO@H (i.e., NSO / LDH@H) has the strongest killing ability on tumor cells, indicating that ZF / NSO@H in this case can indeed be used in the preparation of anti-tumor preparations or anti-tumor materials.

[0051] Figure 7The figure shows the biocompatibility of ZF / NSO@H. It can be seen that ZF / NSO@H has good biocompatibility. When the concentration of the hydrogel is 400μg / ml (based on the concentration of Na2S2O8 contained in the hydrogel), the survival rate of tumor cells drops to about 20%, but the change in hydrogel concentration has no effect on normal cells L929.

[0052] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. An injectable hydrogel system, characterized in that: The injectable hydrogel system is mainly composed of silk fibroin and loaded with layered metal double hydroxide ZnFe-LDH and sodium peroxymonosulfate nanoparticles Na2S2O8 NPs, wherein the concentration ratio of ZnFe-LDH to Na2S2O8 NPs is 1:4-1:

8.

2. A method for preparing the injectable hydrogel system according to claim 1, characterized in that: The amino acid surfactant is dissolved in an aqueous solution of layered metal double hydroxide ZnFe-LDH and activated, and injectable silk fibroin is added. After the injectable silk fibroin is dissolved, an aqueous solution of sodium peroxymonosulfate nanoparticles Na2S2O8 NPs is added and waited until gelation occurs to obtain an injectable hydrogel system.

3. The method for preparing an injectable hydrogel system according to claim 2, characterized in that: The molecular weight of the injectable silk fibroin is 10-15 kDa.

4. The method for preparing an injectable hydrogel system according to claim 2, characterized in that: The amino acid surfactant is lauroyl arginine hydrochloride, sodium lauroyl glutamate, sodium dodecyl sulfate or sodium cholate hydrate.

5. The method for preparing an injectable hydrogel system according to claim 2, characterized in that: The activation temperature is 40~60 ℃, and the activation time is 4~6 min.

6. The method for preparing an injectable hydrogel system according to claim 2, characterized in that: The preparation method of the injectable silk fibroin is as follows: boiling a Na2CO3 aqueous solution, adding silkworm cocoons and boiling, replacing the Na2CO3 aqueous solution with a new one for boiling and degumming, washing with deionized water, drying, and obtaining degummed silk fibroin; adding a lithium bromide solution to dissolve the degummed silk fibroin to obtain a completely dissolved silk fibroin solution, placing the solution in a dialysis bag, and dialyzing at room temperature; and finally freeze-drying to obtain the injectable silk fibroin.

7. The method for preparing an injectable hydrogel system according to any one of claims 2 to 6, characterized in that: The preparation method of the layered metal double hydroxide ZnFe-LDH is as follows: adding a mixed aqueous solution of NaOH and Na2CO3 dropwise into a mixed aqueous solution of Fe(NO3)3·9H2OH and Zn(NO3)2·6H2O within 2 hours, controlling the pH, aging the obtained suspension, centrifugally collecting, washing, and vacuum drying to obtain ZnFe-LDH powder. In the mixed aqueous solution of Fe(NO3)3·9H2OH and Zn(NO3)2·6H2O, the molar ratio of Zn / Fe is 2:1-4:

1.

8. The method for preparing an injectable hydrogel system according to any one of claims 2 to 6, characterized in that: The preparation method of the sodium peroxymonosulfate nanoparticles Na2S2O8 NPs is as follows: oleylamine and sodium oleate are added to a mixed solution of n-hexane and anhydrous ethanol, and after the oleylamine and sodium oleate are completely dissolved, ammonium persulfate is added, and after the ammonium persulfate is completely dissolved, centrifugation is performed, and washing is performed to obtain the sodium peroxymonosulfate nanoparticles Na2S2O8 NPs. The volume ratio of oleylamine, n-hexane, and anhydrous ethanol is 1:10:3; The mass ratio of sodium oleate to ammonium persulfate is 3:2~2:

1.

9. The method for preparing an injectable hydrogel system according to claim 8, characterized in that: Washing refers to washing with n-hexane and anhydrous ethanol.

10. An application of the injectable hydrogel system according to claim 1, characterized in that: The injectable hydrogel system is used for the preparation of drug sustained-release preparations and anti-tumor preparations.